New Delhi metallo-β-lactamase–producing Escherichia coli among dogs at an animal rescue facility—Wisconsin, 2022 - Kiara McNamara; Caroline Habrun; W. Wyatt Wilson; Leslie Kollmann; G. Sean Stapleton; Richard Stanton; Katharine Benedict; Amanda Beaudoin; Paula Snippes; Melissa Anacker; Megin Nichols; Maroya Walters; et al. (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
Background: New Delhi Metallo-β-lactamase (NDM)–producing Escherichia coli are highly resistant organisms that spread quickly. In the United States, organisms with blaNDM are rare and mostly associated with healthcare settings. However, in other countries, blaNDM can be relatively common and are found in community settings. State veterinary and public health partners detected NDM E. coli in a dog from Iran living at a Wisconsin animal rescue facility (ARF), where 40% of dogs had international origins. We investigated to determine spread among dog and human contacts and prevent further transmission. Methods: We screened dogs and humans at the ARF, a local veterinary clinic (clinic A), and ARF staff homes (homes A and B) for colonization with blaNDM. We reviewed veterinary records and conducted a case–control analysis to identify risk factors for blaNDM acquisition among dogs. We evaluated ARF infection control practices. Screening specimens that were positive for blaNDM were cultured. We conducted an analysis of short- and long-read whole-genome sequencing data to evaluate isolate relatedness. We compared NDM E. coli sequences from dogs to all NDM E. coli sequences from humans collected in Wisconsin and nearby states. Results: Screening identified blaNDM colonization in 27 (37%) of 73 ARF dogs and 4 (56%) of 7 dogs in home A, but not in ARF or staff in clinic A. Among ARF dogs with blaNDM, 20 (74%) 27 had international origins and 22 (81%) had ≥1 medical condition. Dogs sharing the same space (OR, 5.1; 95% CI, 1.8–14.7) were associated with blaNDM acquisition. We observed high animal density, soiled environments, and insufficient hand hygiene. ARF staff wore workwear and work shoes off site, including to home A. Sequencing identified 3 multilocus sequence types (STs) using the Achtman scheme among 27 isolates with blaNDM-5. Most isolates were ST361 (20 of 27, 74%) followed by ST167 (6 of 27, 22%) and ST1163 (1 of 27, 4%). Within-MLST cluster variability was <1–3 high-quality single-nucleotide variant differences, each harboring a ST-specific plasmid with blaNDM-5. No NDM-E. coli sequences from humans appeared related. Conclusions: Investigation of a single isolate led to identification of widespread NDM-E. coli transmission among dogs at an ARF. There were multiple NDM E. coli introductions to the ARF, likely by dogs of international origin. Poor hygiene contributed to transmission among ARF dogs and to dogs outside the ARF. Transmission of blaNDM-5 at the ARF and offsite spread to home A demonstrate the potential for unrecognized community sources to disseminate NDM E. coli in community settings. Strategies and lessons learned from interventions to prevent antibiotic resistance in human healthcare settings may inform and support prevention in animal care.